Low Carbon Economic Production Quantity Model for Imperfect Quality Deteriorating Items - Daryanto, Y; Wee, H.M. (Universitas Atma Jaya Yogyakarta, 2019)
This paper presents an economic production quantity (EPQ) model for deteriorating items with a certain percentage of defective products due to an imperfect process. The defective products are sold to a secondary market at a discount price. Due to environmental concern and carbon tax regulation, the manufacturer incorporates the control of carbon emission cost into its decision model. Carbon emission cost is a function of electricity consumption during production and inventory storage; it is also dependent on the carbon tax rate. Since the production process results in work-in-process inventory and carbon emission, the study tries to optimize the throughput time. We also examine the effect of carbon tax regulation on the potential emission reduction from the developed deteriorating item model. A numerical example and sensitivity analysis have been provided, and the result confirms the influence of carbon tax regulation in reducing carbon emission.